Redescription of Rhyacophila clemens Tsuda 1940 (Trichoptera, Rhyacophilidae), with descriptions of five new, allied species from Japan - Kawase, Naoki (Zootaxa, 2024)
Japanese species of the Rhyacophila clemens Species Group Ross 1956 are revised, and six species including five new allied species are recognized: R. clemens Tsuda 1940, R. vesperalis sp. nov., R. inazui sp. nov., R. angulicauda sp. nov., R. parvicauda sp. nov., and R. furcicauda sp. nov. Adult males and females of all species are described or redescribed, and the male genitalia of a Korean species, R. kumgangsanica Kumanski 1990, also belonging to this species group, are illustrated for comparison. The lectotype of R. clemens is designated for nomenclatural stability. The main diagnostic characters for the R. clemens Species Group are provided as follows: (1) Segment X bears an apical hinged process posteroventrally; (2) two pairs of anal sclerites have a common internal root; (3) a pair of large apical bands surrounds the anus and the root of the anal sclerites; (4) the aedeagus bears a large sclerotized ventral plate.